Investigating volatiles as the secondary metabolome of Piper methysticum from root powder and water extracts using comprehensive two-dimensional gas chromatography. (10th August 2022) - Cheung, Cynthia; Baker, Jonathan D.; Byrne, Julianne M.; Perrault, Katelynn A.
Abstract: Ethnopharmacological relevance: Kava ( Piper methysticum G. Forst) is a plant grown in the Pacific that is used in traditional medicines. The roots are macerated and powdered for consumption as a beverage in social settings as well as in ceremonies. Other types of preparations can also be used as traditional medicines. There has been an increase in demand for kava as there is continued traditional use and as it is becoming utilized more both socially and medicinally outside of Oceania. Currently, most research of this plant has focused on bioactive kavalactones and flavokawains, and there are few studies focusing on the other compounds that kava contains, such as volatile and semivolatile components. Aim of the study: This study investigated the kava volatile organic compound (VOC) profile from nine different commercially available samples of dried, powdered kava root sourced across the Pacific region. Materials and methods: The headspace above the kava samples was analyzed, both from the root powder as originally purchased and by performing a scaled-down extraction into water mimicking traditional preparation of the beverage. The headspace of each sample was extracted using solid-phase microextraction arrow (SPME Arrow), followed by analysis using comprehensive two-dimensional gas chromatography – quadrupole mass spectrometry/flame ionization detection (GC×GC-qMS/FID). The superior peak capacity of GC×GC was invaluable in effectively separating the complex mixture of compounds found in all samples, which enabled improved monitoring of minor differences between batches. Results: Dry root powder samples contained high levels of β-caryophyllene while water extracted samples showed high levels of camphene. Many alcohols, aldehydes, ketones, terpenes, terpenoids, and aromatics were also characterized from both types of samples. All water extracted samples from the different brands followed similar trends in terms of compounds being detected or not. Additional major compounds found in water extracts included benzaldehyde, hexanal, methoxyphenyloxime, camphor, limonene, 1-hexanol, endoborneol, and copaene. While some samples could be differentiated based on brand, samples did not group by purported geographic origin. Conclusions: This study provides foundational data about a different subset of compounds within kava than previous research has studied, and also informs the community of the compounds that transfer into the consumed beverage during the traditional means of preparing kava. Graphical abstract: Image 1 Highlights: This study presents the volatile organic compound profile of kava. Dry kava powder contained high levels of β-caryophyllene. Water extracted kava contained high levels of camphene. One third of the chemical profile consisted of terpenes and terpenoids. Review of terpene pharmacological benefits to explore kava's therapeutic effects.